(untitled) (Veterinary Science, 2017)
Studies have proved that humoral immune response is involved in swine pregnancy. Pigs have IgG, IgM, IgA and IgE. Swine IgG subclasses have their greatest similarity with those of the human, except for the near absence of hinge region variation. The goal of this study was to determine the presence of IgG in porcine serum, tissue and placental extracts. In 15 animals’ serum, by means of electrophoresis proteinegramma in strips of cellulose acetate, the average values were empty pig (n=5) 23mg/ml; 30 days (n=5) 19.5mg/ml; and 91 days of gestation (n=5) 16.8 mg/ml. By radial immunodifusion (using calibrated commercial human kits to determine the concentration of human IgG), the average values in porcine serum (n=15) were non-pregnant swine 26.88 mg/ml; 30 days 29.88 mg/ml; 91 days of gestation 19.24 mg/ml. In placental extracts, Porcine Empty Uterus Homogenates: 3.40 mg/ml; Porcine Placenta Homogenates (PPHo) 30 days: 1.81mg/ml; PPHo 91 days: 1.50 mg/ml. and in Porcine Placenta Conditioned Medium (PPCM) 30 days: 2.11 mg/ml and PPCM 91 days of gestation: 1.20 mg/ml. By direct immunofluorescencia, using one antibody (human anti-IgG conjugated with FITC), we observed: fluorescence (++) on placental tissues at term, in the foetal chorionics villi in contact with the uterine lumen. Probably these antibodies belong to the type of protective and asymmetric immunoglobulin G antibodies described in woman and mouse